Direct communication between radiologists and patients following imaging examinations: should radiologists rethink their patient care? - Gutzeit, Andreas; Janssen, Sonja (European radiology, 2019)
ObjectivesTo investigate patients’ perception of the radiology service when the radiologist communicates the findings to patients.MethodsAfter routine MRI, patients in group 1 (n = 101) were given the opportunity to discuss the findings with the radiologist. Patients in group 2 (n = 101) left the radiology department without any personal communication. Subsequently, by means of a questionnaire designed by an expert psychologist, both groups were asked regarding their anxiety, emotional attachment to the institute and subjective assessment of competence.ResultsOverall 76 % of all patients were concerned about their imaging findings without significant difference between both groups (p = 0.179). Significantly more patients in group 1 (81%) versus group 2 (14%; p < 0.001) perceived the opportunity to discuss their imaging findings with a radiologist to be a characteristic of a good radiology consultation. A larger number of patients in group 1 experienced significantly higher bonding and only wanted in the future to be examined in the department with communication (p = 0.001) (93%/75%). Significantly more patients in group 1 regarded the radiology department they attended as being more competent (mean score 4.72/4.09, p < 0.001).ConclusionDirect communication of imaging findings from radiologists to patients after an MRI examination leads to increased confidence in the radiology service and higher bonding between the patient and radiologist. Radiologists who refrain from direct communication have a lower bonding to patients and are assessed to have lower competence from the patient’s point of view.Key Points • Communication between radiologists and patients leads to an increased bonding affinity. • Direct communication leads to increased patient confidence in the radiology service. • Patients perceived discussion with a radiologist of high value.
Published online: 25 June 2018
Gesehen am 02.08.2019